Download presentation

Presentation is loading. Please wait.

Published byShon Rogers Modified over 6 years ago

1
SECTION 6.1 SYSTEMS OF LINEAR EQUATIONS: SYSTEMS OF LINEAR EQUATIONS: SUBSTITUTION AND ELIMINATION SUBSTITUTION AND ELIMINATION

2
MOVIE THEATER TICKET SALES SEE EXAMPLE 1 SEE EXAMPLE 2

3
EQUIVALENT SYSTEMS OF EQUATIONS Linear System More than one linear equation considered at a time. Solution - ordered pair (or triple) that satisfies both (or all) equations simultaneously.

4
CONSISTENT VS. INCONSISTENT When a system of equations has at least one solution, it is said to be consistent; otherwise, it is called inconsistent.

5
THREE POSSIBILITIES FOR A LINEAR SYSTEM x - y = 1 x - y = 3 No Solution x - y = 1 2x - y = 4 One Solution x - y = 1 2x - 2y = 2 Infinitely Many Solutions

6
SOLVING A SYSTEM BY SUBSTITUTION 2x + y = 5 - 4x + 6y = 12

7
RULES FOR OBTAINING AN EQUIVALENT SYSTEM 1.Interchange any two equations. 2.Multiply (or divide) each side of an equation by a nonzero constant. 3.Replace any equation in the system by the sum (or difference) of that equation and a nonzero multiple of any other equation in the system.

8
SOLVING A SYSTEM BY ELIMINATION 2x + 3y = 1 -x + y = - 3 Multiply equation 2 by 2 Replace equation 2 with the sum of equations 1 and 2.

9
MOVIE THEATER TICKET SALES DO EXAMPLE 5

10
AN INCONSISTENT SYSTEM 2x + y = 5 4x + 2y = 8

11
AN DEPENDENT SYSTEM 2x + y = 4 - 6x - 3y = - 12

12
3 EQUATIONS, 3 UNKNOWNS 2 x + 4y - 2 z = - 10 - 3x + 4y - 2 z = 5 5x + 6y + 3 z = 3 Dividing 1st equation by 2 to make leading coefficient equal to 1. x + 2 y - z = - 5 x + 2 y - z = - 5 - 3x + 4y - 2 z = 5 5x + 6y + 3 z = 3

13
EXAMPLE x + 2 y - z = - 5 x + 2 y - z = - 5 - 3x + 4y - 2 z = 5 Mult. 1st eqn by 3 and add to 2nd 3x + 6 y - 3 z = - 15 3x + 6 y - 3 z = - 15 - 3x + 4y – 2z = 5 - 3x + 4y – 2z = 5 10y – 5z = -10 10y – 5z = -10

14
EXAMPLE x + 2 y - z = - 5 x + 2 y - z = - 5 5x + 6y + 3 z = 3 Mult. 1st eqn by -5 and add to 3rd -5x - 10 y + 5 z = 25 -5x - 10 y + 5 z = 25 5x + 6y + 3z = 3 5x + 6y + 3z = 3 - 4y + 8z = 28 - 4y + 8z = 28

15
EXAMPLE Now we have 2 equations in only y & z: 10y - 5 z = -10 - 4y + 8 z = 28 Divide 1 st equation by 5 Divide 2nd equation by 4

16
EXAMPLE 2y - z = - 2 - y + 2 z = 7 Multiply 2 nd equation by 2 & add to 1st 2y – z = -2 -2y + 4z = 14 3z = 12 3z = 12 z = 4 z = 4

17
EXAMPLE 2y – z = -2 2y – z = -2 2y – 4 = -2 2y – 4 = -2 2y = 2 2y = 2 y = 1 y = 1 x + 2y – z = - 5 x + 2 (1) - 4 = - 5 x - 2 = - 5 x = - 3 (-3, 1, 4)

18
EXAMPLE DO EXAMPLES 9, 10, 11 DO EXAMPLES 9, 10, 11

19
CONCLUSION OF CONCLUSION OF SECTION 6.1 SECTION 6.1

Similar presentations

© 2021 SlidePlayer.com Inc.

All rights reserved.

To make this website work, we log user data and share it with processors. To use this website, you must agree to our Privacy Policy, including cookie policy.

Ads by Google